TINGKAT KEPATUHAN PASIEN TUBERKULOSIS PARU PADA PENGGUNAAN OBAT ANTI TUBERKULOSIS DI PUSKESMAS CIPAYUNG KOTA DEPOK - Agung Dewantoro; Aulia Nadya Rizki Imansari; Ahmad Fadhila (PHRASE (Pharmaceutical Science) Journal, 2022)
Tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis, which can attack the lungs and other organs. Transmission occurs when a person inhales droplet nuclei that enter through the mouth or nose, upper respiratory tract and bronchi until they reach the lungs. One of the determinants of success in the treatment of pulmonary TB is that the patient must improve compliance in taking anti-tuberculosis drugs obediently and regularly until complete. There are several factors that influence the level of adherence to the use of anti-tuberculosis drugs in patients with pulmonary TB, namely motivation, family support, supervision from PMO, education level and occupation. This study aims to determine the level of adherence to the use of anti-tuberculosis drugs in pulmonary TB patients at the Cipayung Health Center. The type of research used is descriptive by using the total sampling method and the sample used is 28 respondents. Data were collected using a validated questionnaire based on the MMAS-8 (Morisky Medication Adherence Scale). The results of this study were (57%) male samples, (36%) were early adults between 26-35 years old, (57%) had high school education, (53.5%) worked as private employees. And the results obtained (82%) have a high level of compliance, (14%) have a moderate level of compliance, and (4%) have a low level of compliance. The conclusion from the level of adherence to the use of anti-tuberculosis drugs in pulmonary TB patients at the Cipayung Health Center with a value (82%) has a high level of adherence as many as 23 respondents.